Synthesis of Spirocyclic and Fused Cyclic Compounds by Transition-Metal-Catalyzed Intramolecular Friedel–Crafts-Type Reactions of Phenol Derivatives - Nemoto, Tetsuhiro; Hamada, Yasumasa (Synlett, 2016)
This account describes the development of novel dearomatization reactions of phenols using transition-metal-catalyzed ipso-Friedel–Crafts-type processes. In general, phenols function as O-nucleophiles in transition-metal-catalyzed allylic substitution reactions, providing the corresponding aryl ethers. We found that, however, an intramolecular ipso-Friedel–Crafts allylic alkylation of phenols proceeded smoothly in the presence of a palladium catalyst, producing various spiro[4.5]cyclohexadienone derivatives. This finding led us to launch detailed investigations into this type of reaction. Pd-catalyzed intramolecular Friedel–Crafts allylic alkylation of phenols was next examined to synthesize 10-vinyl 9,10-dihydrophenanthrene derivatives. This reaction was successfully extended to a catalytic asymmetric process. We also developed a novel synthetic method for spiro[5.5]cyclohexadienones based on a Pd-catalyzed intramolecular ipso-Friedel–Crafts-type addition of phenols to η3-propargylpalladium(II) intermediates. Mechanistic studies revealed that the present reaction proceeds through a rearomatization-assisted oxidative addition. Moreover, a Au-catalyzed intramolecular ipso-Friedel–Crafts alkenylation of phenols with a terminal alkyne is discussed.1 Introduction2 Pd-Catalyzed Intramolecular Friedel–Crafts Allylic Alkylation of Phenols2.1 Synthesis of Spirocyclohexadienone Derivatives by Pd-Catalyzed Intramolecular ipso-Friedel–Crafts Allylic Alkylation of Phenols2.2 Mechanistic Considerations2.3 Application to Cascade Reaction Processes2.4 Asymmetric Synthesis of Dihydrophenanthrene Derivatives by Pd-Catalyzed Asymmetric Intramolecular Friedel–Crafts Allylic Alkylation of Phenols3 Dearomatization of Phenols by Activation of Propargyl Carbonates with a Pd Catalyst4 Au-Catalyzed Intramolecular ipso-Friedel–Crafts Alkenylation of Phenols5 Summary and Outlook
Keywords: asymmetric catalysis; dearomatization; Friedel–Crafts reaction; fused ring system; spiro compounds; transition-metal catalysis